Co-fermentation of residual algal biomass and glucose under the influence of Fe3O4 nanoparticles to enhance biohydrogen production under dark mode. (December 2021) - Srivastava, Neha; Srivastava, Manish; Singh, Rajeev; Syed, Asad; Bahadur Pal, Dan; Elgorban, Abdallah M.; Kushwaha, Deepika; Mishra, P.K.; Gupta, Vijai Kumar
Graphical abstract: Highlights: Co-fermentation of residual algal biomass and glucose under the influence of Fe3 O4 NPs. Fe3 O4 NPs leads ∼ 37.14 % higher cumulative H2 as compared to control at 37 °C. ∼ 11.28 % higher hydrogen production at optimum temperature in presence of Fe3 O4 NPs. Evaluates hydrogen production at different pH in presence of Fe3 O4 NPs. Potential of nanomaterials induced enhanced hydrogen production using co-fermentation. Abstract: The present study reports Fe3 O4 nanoparticles (Fe3 O4 NPs) induced enhanced hydrogen production via co-fermentation of glucose and residual algal biomass (cyanobacteria Lyngbya limnetica ). A significant enhancement of dark fermentative H2 production has been noticed under the influence of co-fermentation of glucose and residual algal biomass using Fe3 O4 NPs as catalyst. Further, using the optimized ratio of glucose to residual algal biomass (10:4), ∼ 37.14 % higher cumulative H2 has been recorded in presence of 7.5 mg/L Fe3 O4 NPs as compared to control at 37 °C. In addition, under the optimum conditions [glucose to residual algal biomass ratio (10:4)] presence of 7.5 mg/L Fe3 O4 NPs produces ∼ 937 mL/L cumulative H2 in 168 h at pH 7.5 and at temperature 40 °C. Clostridum butyrium, employed for the dark fermentation yielded ∼ 7.7 g/L dry biomass in 168 h whereas acetate (9.0 g/L) and butyrate (6.2 g/L) have been recorded as the dominating metabolites.